"A gentle balance of pushing, pulling and sitting with": An interpretative phenomenological analysis of psychological therapists' experiences of working with goals in adult pluralistic private practice. Issue 1 (2nd January 2022) - Lloyd, Christopher E. M.; Antonino, Raffaello
ABSTRACT: Evidence suggests that working with goals, or goal-based practice (GBP) which is fundamental to several contemporary psychotherapies, can enhance the content, process and outcome of psychotherapeutic work. At present, no qualitative research has explored how psychological therapists experience GBP with their clients. Interpretative phenomenological analysis (IPA) was selected to explore how eight psychological therapists working in adult pluralistic private practice experienced GBP. Three superordinate themes were constructed during the analysis process. "A pathway through the jungle" highlighted how GBP was variously experienced as aiding the therapeutic partnership by monitoring progress, providing focus and increasing positive affect. "Invalidating the therapeutic journey, " where GBP was felt to potentially detract from the client's frame of reference, to jeopardise the therapeutic containment of sessions and increase the client's feeling of failure. Finally, "Maintaining the client-led story, " which resembled an antidote to what was experienced as non-humanistic GBP. This involved practitioners preserving time to reflect on their own goals and agendas for their clients and the ways their own psychological processes might be influencing the use of GBP within the therapeutic relationship. Of particular pertinence was therapists' acknowledgement that GBP may function to shield therapists from feelings of failure or frustration, and may be used consciously or otherwise. We argue that approaches to GBP that attempt to determine helpful or unhelpful aspects of GBP in isolation are likely to overlook therapeutic processes which are vital to ensuring that GBP is collaborative and meaningful for the client. Results are discussed regarding wider literature and suggestions for further research are made.